(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The pursuit of a sustainable fitness program is viewed as a global issue and mission. Clearly, this is a global problem, and it should be prioritized as the first step in any health-care program. It is the value, knowledge, talents, and experiences obtained via physical activity in order to achieve and maintain health-related fitness and maximize health. This study examines what factors motivate MAPEH instructors to exercise. There are 72 MAPEH teachers from Zamboanga City’s top eight (8) schools participated in the research. The findings reveal that respondents demonstrated above-average level on Identified Regulation motivating component. MAPEH teachers choose to exercise freely because they appreciate the benefits of exercise. They like exercise sessions, regard physical activity as a pleasurable pastime, and receive pleasure and fulfillment from physical activity. The respondents in this study do not believe they should exercise because other people, such as friends/family/partner, have pushed them to do so. This study revealed that exercising is a personal responsibility of someone for health, social belonging, and personal development. This study is very vital in analyzing the features of exercise and how active participants are motivated to consistently doing the practice. The information from this study can help program fitness programs for the faculty and other employees of organizations with similar profile.